The Implementation of Project based Learning in Physical Education at Elementary Schools - Dewi Septaliza; Muslimin Muslimin; Dwi Susilo Nugroho (UNIB Press, 2024)
The Implementation of Project Based Learning as an Innovative Learning Approach in the Context of Physical Education at Elementary Schools. This research employs a qualitative approach with a case study research design. It was conducted at SD Negeri 75 Palembang, Grade V. Data was collected through observation, interviews, and document analysis. Thematic data analysis was utilized to identify patterns in learning outcomes and student responses to this learning approach. The results of the study indicate that the implementation of PjBL in physical education at the elementary level positively contributes to students' understanding of concepts, critical thinking skills, collaborative skills, and motivation to learn. Projects designed in real-world contexts provide students with deep and relevant learning experiences, thereby enhancing their engagement in learning. Additionally, learning through PjBL also offers teachers opportunities to observe students' holistic development and provide appropriate feedback. In conclusion, the application of PjBL in physical education at the elementary level is effective in enhancing students' understanding of concepts and their engagement. Recommendations from this research include further training for teachers in designing and implementing meaningful projects, as well as broader integration of the PjBL approach into the Physical Education curriculum at the elementary school level.